Militarizing Outer Space
XXVI, 443 p. 53 illus., 29 illus. in color.
Keywords: Militarizing Outer Space explores the dystopian and destructive dimensions of the Space Age and challenges conventional narratives of a bipolar Cold War rivalry. Concentrating on weapons, warfare and vio lence, this provocative volume examines real and imagined endeavors of arming the skies and conquering the heavens. The third and final volume in the groundbreaking European Astroculturetrilogy, Militarizing Outer Space zooms in on the interplay between security, technopolitics and knowledge from the 1920s through the 1980s. Often hailed as the site of heavenly utopias and otherworldly salvation, outer space transformed from a promised sanctuary to a present threat, where the battles of the future were to be waged. Astroculture proved instrumental in fathoming forms and functions of warfare’s futures past, both on earth and in space. The allure of dominating outer space, the book shows, was neither limited to the early twenty-first century nor to current American space force rhetorics.